Stem Cell Patenting: Moral and Legal Dilemma (Journal of Intellectual Property Rights (JIPR), 2023)
Humans in the era of 21st century have witnessed development at its epitome, coupled with obvious pros and cons. Their greed has led to over exploitation of resources, causing irreversible damages. Presently, the positive aspects of development seem to overshadow the negatives. Increased life span, mortality rate, better health facilities and treatment of incurable diseases are some affirmative outcomes of development. One such recent phenomenon is stem cell therapy. The credit for the discovery being spotlighted goes to scientists John Gurdon and Shinya Yamanaka, who were awarded the Nobel Prize in 2012 for discovering that ordinary cells of a living organism can be reprogrammed or changed into stem cells, which can further turn into any other tissue of the body. Owing to this breakthrough, the treatment of incurable diseases like cancer does not seem to be a distant dream. However, it is shadowed by concerns from critics on the grounds of morality due to its nature of procuring living components to get patents. In this paper, the author discusses the concept of stem cell therapy, the present legal scenario vis-à-vis its patentability and the ongoing debate regarding legal and moral implications of stem cell patenting.